Deterioration of health of infants during the war and COVID-19 pandemic in Ukraine - O.P. Volosovets; S.P. Kryvopustov; A.Ya. Kuzmenko; M.P. Prokhorova; O.F. Chernii; V.Ye. Khomenko; O.V. Iemets; N.V. Gryshchenko; O.L. Kovalchuk; A.V. Kupkina (Zaslavsky O.Yu., 2024)
Background. The coronavirus disease 2019 (COVID-19) pandemic and the war have significantly affected the state of national medical systems and the health of the population, especially children. The purpose of the study is to analyze the impact of the war and pandemic consequences on the health status of children in the first year of life from 2020 to 2023 in Ukraine. Materials and methods. A retrospective analysis of the birth rate and the number of children in Ukraine, the frequency of breastfeeding, and the morbidity of children in the first year of life in Ukraine from 2020 to 2023 was conducted according to the data of the Public Health Centre of the Ministry of Health of Ukraine. Methods of systematic approach and epidemiological analysis were used. Results. In the last four years during the war and the COVID-19 pandemic, the number of children in Ukraine decreased to 5.5 million, or by 19.3 %, compared to 2020. The number of infants decreased even more, by 43.06 %, due to a 30.5 % decrease in the birth rate compared to 2020 (p < 0.01). The proportion of children who stopped breastfeeding at 3 months increased by 11.67 % between 2020 and 2023, while the number of those who stopped breastfeeding at 6 months decreased slightly, by 3.97 %. The largest increase in the proportion of children who stopped breastfeeding at these ages was observed in the Donetsk, Luhansk and Zaporizhzhia regions, where the most intense hostilities are taking place. An increase in the morbidity rate among children in the first year of life to 1463.5 ‰, or by 19.9 % compared to 2020, and its return to the levels observed in the middle of the last decade indicate the negative impact of direct and indirect war-related factors on the health status of children in the first year of life, and, probably, a limited access to health care in areas where hostilities continue and those been de-occupied. Respiratory diseases, especially acute upper respiratory diseases, pneumonia, influenza, certain perinatal conditions, diseases of the skin and subcutaneous tissues, digestive disorders, nervous system and blood diseases are the main causes of morbidity among children in the first year of life. Conclusions. The war and the consequences of the COVID-19 pandemic have had a negative impact on the birth rate, the number of the child population in Ukraine. Morbidity rates among infants have increased, and breastfeeding rates and vaccination coverage have decreased.